2005
DOI: 10.1002/pds.1124
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of drug use during a 15 year period: data from a Swedish county, 1988-2002

Abstract: The increase in drug prescribing over the 15 years concerned both symptom-related treatments, like hormone replacement therapy, analgesics, antidepressants and drugs for acid-related disorders, as well as preventive treatments, like antithrombotics, lipid-lowering drugs and antihypertensives. The unit DDD/100 inhabitants and day gives a fairly correct measure of the percentage treated for chronic disorders. However, for short-term treatment courses and especially for drug use in children, number of prescriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
4
13
0
2
Order By: Relevance
“…The most commonly dispensed PPI in Norway, esomeprazole, is not commonly used in Sweden nor Denmark. In the Swedish thesis, for several of the cardiovascular drug groups there was a 2-fold difference in sales figures between two neighbouring [7][8][9][10][11][12]. Among other things, the results showed that over the study period, prescribing by general practitioners (gPs) increased both in absolute and relative terms.…”
Section: Master's Degree Theses Related To Pharmacoepidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly dispensed PPI in Norway, esomeprazole, is not commonly used in Sweden nor Denmark. In the Swedish thesis, for several of the cardiovascular drug groups there was a 2-fold difference in sales figures between two neighbouring [7][8][9][10][11][12]. Among other things, the results showed that over the study period, prescribing by general practitioners (gPs) increased both in absolute and relative terms.…”
Section: Master's Degree Theses Related To Pharmacoepidemiologymentioning
confidence: 99%
“…These healthcare providers estimated that approximately one-half of patients are affected by drug-related morbidity, both among outpatients and inpatients [8,9]. Moreover, 24-45% of instances were judged as preventable, and the ensuing costs were estimated to represent up to 20% of total costs to the healthcare system.…”
Section: Fundingmentioning
confidence: 99%
“…Most chronic conditions (comorbidities) are covered by disease-specific clinical guidelines using a single disease framework; this leads physicians to recommend drug treatments for each condition separately, which may lead to polypharmacy and drug-drug and drug-disease interactions [5]. In addition, to lower the risk of developing future medical conditions, research in preventive medicine has uncovered multiple risk factors, particularly in cardiovascular medicine, that also need treatment, thus increasing the number of people on regular multiple drug therapy [6,7]. Furthermore, patients are often seen by multiple specialist physicians who prescribe drugs that primary care physicians are often reluctant to stop [8].Polypharmacy, commonly defined as the concurrent use of 5 or more long-term prescribed drugs, is frequent and increasing in prevalence [4,7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to lower the risk of developing future medical conditions, research in preventive medicine has uncovered multiple risk factors, particularly in cardiovascular medicine, that also need treatment, thus increasing the number of people on regular multiple drug therapy [6,7]. Furthermore, patients are often seen by multiple specialist physicians who prescribe drugs that primary care physicians are often reluctant to stop [8].Polypharmacy, commonly defined as the concurrent use of 5 or more long-term prescribed drugs, is frequent and increasing in prevalence [4,7,[9][10][11][12][13][14]. The use of multiple drugs is associated with potential unforeseen medical consequences, such as adverse drug events, drug monitoring errors, unplanned hospitalizations, and sometimes fatal outcomes [5,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…y día considerando exclusivamente la población mayor de 65 años (el 17% de la población en la Comunidad Valenciana), la cifra aproximada de usuarios diarios de antiagregantes sería del 21% (215 DDD/1.000 habitantes mayores de 65 años y día). Este valor está en el mismo rango que en Suecia donde alrededor del 27% de habitantes de 60 o más años utiliza fárma-cos antitrombóticos 22 .…”
Section: Discussionunclassified